RESEARCH OF SMART TECHNOLOGIES IN THE CONDITIONS OF DIGITALIZATION OF PROCESS OF FORMATION OF ROUTES IN THE CONDITIONS OF EXISTING RESTRICTIONS OF THE INTERNATIONAL TRANSPORT CORRIDORS - Мельник, Александр; Литвинов, Александр; Помазков, Михаил (SWorldJournal, 2021)
In the context of expanding international cooperation and deepening integration processes, the formation of international transport corridors has a leading role in solving transport problems related to interstate economic, cultural and other ties, with th